Kepentingan Umum sebagai Pengecualian pada Tindak Pidana Pencemaran Nama Baik dalam Undang-Undang Informasi dan Transaksi Elektronik - Daniela Sine, Elena; Parabandani, Hendra Wahanu (Neolectura, 2025)
The advancement of science and technology has led to the emergence of new societal frameworks, enabling the rise of new legal actions. Law Number 1 of 2024 on the Second Amendment to Law Number 11 of 2008 on Information and Electronic Transactions, was established as a response to the legal need for regulations governing actions in electronic media, particularly concerning defamation. The regulation of